2014
DOI: 10.14502/tekstilec2014.57.118-132
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Natural Textile Materials in Soil

Abstract: World is facing numerous environmental challenges, one of them being the increasing pollution both in the atmosphere and landfi lls. After the goods have been used, they are either buried or burnt. Both ways of disposal are detrimental and hazardous to the environment. The term biodegradation is becoming more and more important, as it converts materials into water, carbon dioxide and biomass, which present no harm to the environment. Nowadays, a lot of research is performed on the development of biodegradable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 14 publications
4
55
0
Order By: Relevance
“…). This wavenumber appeared with a strong intensity in the ancient damaged sample and this absorption band was also observed in the experimental sample, but in a relatively weak form, resulting in damage to the linen and degradation (Arshad and Mujahid ). The functional groups showed strong relative intensities at 1372 cm −1 , 1336 cm −1 , 1313 cm −1 , 1280 cm −1 , 1160 cm −1 and 1105 cm −1 , which indicated a shift in the cellulose polymer from high‐crystalline to amorphous regions.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…). This wavenumber appeared with a strong intensity in the ancient damaged sample and this absorption band was also observed in the experimental sample, but in a relatively weak form, resulting in damage to the linen and degradation (Arshad and Mujahid ). The functional groups showed strong relative intensities at 1372 cm −1 , 1336 cm −1 , 1313 cm −1 , 1280 cm −1 , 1160 cm −1 and 1105 cm −1 , which indicated a shift in the cellulose polymer from high‐crystalline to amorphous regions.…”
Section: Resultsmentioning
confidence: 60%
“…Subsequently, these changes suggested that the archaeological samples were degraded compared with the experimental sample, and these results were consistent with those reported by Hulleman et al . () and Arshad and Mujahid (). Our results indicated that linen textile is the fibre material used for the cartonnage layers, and this finding is consistent with those of Scott et al .…”
Section: Resultsmentioning
confidence: 97%
“…Biodegradation of cellulosic fabric in soil has been investigated to determine the factors that are correlated to the rate of degradation . Weight loss of the fabric is an important indicator of the degradation process . In a laboratory‐controlled environment, the emission of carbon dioxide also indicated the rate of biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Cellulosic fibres are more susceptible to biodegradation than non-cellulosic fibres due to their 30%-35% amorphous region. 5 Unfortunately, the biodegradation fate of the most commonly used cellulosic dyes-reactive dyes-remains unstudied. The release of reactive dyes and their degradation products can bioaccumulate in the environment, and these are carcinogenic and mutagenic for humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation